Indirect Costs of Financial Distress - Custódio, Cláudia; Ferreira, Miguel A; Garcia-Appendini, Emilia (Review of Finance, 2023)
We estimate the indirect costs of financial distress due to lost sales by exploiting real estate (RE) shocks and cross-supplier variation in RE assets and leverage. We show that for the same client buying from different suppliers, the client’s purchases from distressed suppliers decline by an additional 13% following a drop in local RE prices. The effect is more pronounced in more competitive industries, manufacturing, durable goods, less-specific goods, and when the costs of switching suppliers are low. Our results suggest that clients reduce their exposure to suppliers in financial distress.